Adsorption type fluorine removal agent as well as preparation method and application thereof
By modifying polyaluminum magnesium lanthanum particles as adsorption type fluorine removal agents, the problems of small adsorption capacity and difficulty in regeneration of existing fluorine removal agents are solved, and efficient and environmentally friendly deep fluorine removal effect is achieved.
Patent Information
- Application Number
- CN202510279932.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-24
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-08
AI Technical Summary
The existing adsorption-type fluorine-removing agents have problems such as small adsorption capacity, high treatment cost, inconvenient use, and difficult regeneration, and may cause secondary pollution.
Modified polyaluminum magnesium lanthanum particles are used as adsorption-type fluorine-removing agent, and the sodium silicate solution, polyhydroxy polymer organic matter and metal salt are slowly added to the aqueous hydrochloric acid solution under stirring state to form a modified polyaluminum magnesium lanthanum mixture with multiple functions, and the particles are obtained by solidification by sodium carbonate solution and vacuum freeze-drying.
Deep fluorine removal has been achieved, fluorine removal is below 0.2ppm, the adsorption capacity can reach 480mg/g, and the regeneration is simple, the regeneration efficiency can reach more than 96%, and the material is environmentally friendly and safe.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fluorine-containing wastewater treatment, and specifically relates to an adsorption-type defluorinating agent, a preparation method and use thereof. Background Art
[0002] Endemic fluorosis is an endemic disease that seriously endangers human health, mainly caused by drinking high-fluoride water. How to remove fluoride efficiently and economically has long been an important issue in the fields of environmental protection and public health. Existing fluoride removal technologies mainly include controlling fluoride pollution from the source, chemical precipitation removal, adsorption removal, etc. Among them, adsorption defluoridation agents have attracted much attention due to their simple operation and significant effects. However, traditional adsorption materials such as activated alumina, bone charcoal, serpentine and hydroxyapatite have problems such as small adsorption capacity, high processing costs, inconvenient use, and difficult regeneration, and may even cause secondary pollution.
[0003] Therefore, it is particularly urgent to develop an adsorption-type defluorination agent that is easy to use, efficient and regenerable. Summary of the invention
[0004] The purpose of the present invention is to provide an adsorption type defluorination agent and a preparation method and application thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing an adsorption-type defluorinating agent comprises the following steps: (1) While stirring, slowly add sodium silicate solution to the hydrochloric acid aqueous solution to control the pH to 3-5.
[0006] (2) Gradually add polyhydroxy polymer organic matter, stir to dissolve, and react for 1 to 3 hours to obtain modified polysilicic acid.
[0007] (3) Add a water-soluble dispersant to the modified polysilicate, and then gradually add aluminum salt, magnesium salt, and lanthanum salt, and stir well to obtain a modified polysilicate aluminum magnesium lanthanum mixed solution.
[0008] (4) Add the modified polysilicate aluminum magnesium lanthanum mixture drop by drop into the sodium carbonate solution and soak for 12 to 24 hours.
[0009] (5) Rinse with pure water, control the surface moisture, first put it into the freezer of the refrigerator for pre-freezing, and then put it into a vacuum freeze dryer for freeze-drying to obtain the adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
[0010] Wherein, in step (1), the mass fraction of the hydrochloric acid aqueous solution is 10% to 25%, preferably 20%.
[0011] Wherein, in step (1), the concentration of the sodium silicate solution is 0.3-1 mol / L, preferably 0.5 mol / L.
[0012] Wherein, in step (2), the polyhydroxy high molecular organic matter is one or more of water-soluble chitosan, sodium carboxymethyl cellulose, sodium alginate, pectin, and polyvinyl alcohol, preferably water-soluble chitosan, with a deacetylation degree of ≥85%.
[0013] Wherein, in the step (2), the amount of polyhydroxy polymer organic matter added is 0.5% to 3%, preferably 2%; and the reaction time is preferably 2h.
[0014] Wherein, in the step (3), the dispersant is one or more of polyethylene glycol, lignin sulfonate, polyethylene imine, and dodecyl dimethyl betaine, preferably polyethylene glycol (average molecular weight of 400-4000), more preferably polyethylene glycol (average molecular weight of 600).
[0015] Wherein, in the step (3), the amount of dispersant added is 0.2% to 2%, preferably 1.2%.
[0016] Wherein, in the step (3), the aluminum salt is one or more of crystalline aluminum chloride, anhydrous aluminum chloride, polyaluminum chloride, polysulfide aluminum chloride, polyaluminum ferric chloride, basic aluminum chloride, aluminum sulfate, polyaluminum sulfate, alum, and aluminum nitrate; the magnesium salt is one or more of magnesium chloride hexahydrate, magnesium carbonate, magnesium sulfate, magnesium nitrate, and magnesium citrate; and the lanthanum salt is one or more of lanthanum chloride, lanthanum nitrate, lanthanum carbonate, lanthanum sulfate, and lanthanum oxalate.
[0017] Wherein, in step (3), n (Si) :n (Al) :n (Mg) :n (La) =1:1.5~2.5:0.5~1.5:0.3~0.8, preferably n (Si) :n (Al) :n (Mg) :n (La) =1:1.5~2:1~1.5:0.5~0.8, preferably n (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1:0.8.
[0018] Wherein, in step (4), the mass concentration of sodium carbonate is 10% to 25%, preferably 20%; and the soaking time is preferably 24 hours.
[0019] Wherein, in the step (5), the freeze-drying temperature is -50 to -70°C, and the freeze-drying time is 12 to 24 hours.
[0020] Experimental studies of the present invention show that the higher the deacetylation degree of chitosan, the better the water solubility and the lower the viscosity; at the same time, the water-soluble chitosan contains a large number of hydroxyl and amino groups, is positively charged, and can form a cross-linked network with negatively charged silicate compounds through electrostatic interaction and hydrogen bonding; then metal ions are added in the presence of a dispersant PEG-600, so that the metal ions are embedded in the cross-linked network and the system is prevented from condensing, forming a cross-linked network with a large number of electrophilic sites (wherein lanthanum has a relatively high affinity for fluorine), and the substance can perform electrical neutralization, ion exchange, adsorption and capture with fluoride ions.
[0021] The present invention uses sodium carbonate solution for solidification, which is cheap; sodium carbonate has weaker alkalinity than sodium hydroxide and will not cause excessive re-dissolution of aluminum salt and lanthanum salt, and is less polluting than ammonia water.
[0022] The present invention adopts a vacuum freeze-drying method, which can fix free water. The volatilization rate is slow during freeze-drying, and the pore structure existing when the free water evaporates is retained, which can improve the adsorption capacity of the defluorinating agent.
[0023] In summary, this material has multiple functions such as electrical neutralization, ion exchange, adsorption capture, and pore adsorption, which make it have excellent adsorption and fluorine removal effect, and the material is environmentally friendly and safe.
[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) The adsorption-type defluoridation agent of the present invention has multiple types of effects and achieves deep defluoridation, which can remove fluorine to below 0.2 ppm.
[0025] (2) The adsorption capacity of the adsorption-type defluorination agent of the present invention can be as high as 480 mg / g. At the same time, the regeneration is simple, and only needs to be backwashed with 2% sodium carbonate solution. The regeneration efficiency can reach more than 96%. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] (1) While stirring, slowly add 145 mL of 0.3 mol / L sodium silicate solution to 100 mL of 10% hydrochloric acid aqueous solution. The pH value is measured to be 4.02.
[0029] (2) Gradually add 0.5% water-soluble chitosan (deacetylation degree > 85%), stir to dissolve, and react for 1 hour to obtain modified polysilicic acid.
[0030] (3) Add 0.2% PEG-4000 to the modified polysilicic acid and then (Si) :n (Al) :n (Mg) :n (La) =1:2:1.5:0.5, gradually add aluminum salt, magnesium salt and lanthanum salt, stir well and evenly to obtain a modified polysilicate aluminum magnesium lanthanum mixed solution. Among them, the aluminum salt is polyaluminum chloride, the magnesium salt is magnesium chloride hexahydrate, and the lanthanum salt is lanthanum chloride.
[0031] (4) Add the modified polysilicate aluminum magnesium lanthanum mixed solution drop by drop into 500 mL of 10% mass concentration sodium carbonate solution and soak for 24 hours.
[0032] (5) Rinse with pure water, control the surface moisture, first put it into the freezer of the refrigerator for pre-freezing for 24 hours, and then put it into a vacuum freeze dryer at -50°C for freeze-drying for 24 hours to obtain the adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
[0033] Example 2
[0034] (1) While stirring, slowly add 110 mL of 0.5 mol / L sodium silicate solution to 100 mL of 15% hydrochloric acid aqueous solution. The pH value is measured to be 3.68.
[0035] (2) Gradually add 1% water-soluble chitosan (deacetylation degree 90%), stir to dissolve, and react for 2 hours to obtain modified polysilicic acid.
[0036] (3) Add 0.7% PEG-2000 to the modified polysilicic acid and then (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1.5:0.6 Gradually add aluminum salt, magnesium salt and lanthanum salt, stir well to obtain a modified polysilicate aluminum magnesium lanthanum mixed solution. Among them, the aluminum salt is polyaluminum chloride, the magnesium salt is magnesium chloride hexahydrate, and the lanthanum salt is lanthanum chloride.
[0037] (4) Add the modified polysilicate aluminum magnesium lanthanum mixed solution drop by drop into 500 mL of 15% mass concentration sodium carbonate solution and soak for 24 hours.
[0038] (5) Rinse with pure water, control the surface moisture, first put it into the freezer layer of the refrigerator for pre-freezing for 24 hours, and then put it into a vacuum freeze dryer at -60°C for 24 hours to obtain the adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
[0039] Example 3
[0040] (1) While stirring, slowly add 170 mL of 0.5 mol / L sodium silicate solution to 100 mL of 20% hydrochloric acid aqueous solution. The pH value is measured to be 3.42.
[0041] (2) Gradually add 2% water-soluble chitosan (deacetylation degree 90%), stir to dissolve, and react for 2 hours to obtain modified polysilicic acid.
[0042] (3) Add 1.2% PEG-600 to the modified polysilicic acid and then (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1:0.8, gradually add aluminum salt, magnesium salt and lanthanum salt, stir well and evenly to obtain a modified polysilicate aluminum magnesium lanthanum mixed solution. Among them, the aluminum salt is polyaluminum chloride, the magnesium salt is magnesium chloride hexahydrate, and the lanthanum salt is lanthanum chloride.
[0043] (4) Add the modified polysilicate aluminum magnesium lanthanum mixed solution drop by drop into 500 mL of 20% mass concentration sodium carbonate solution and soak for 24 hours.
[0044] (5) Rinse with pure water, control the surface moisture, first put it into the freezer layer of the refrigerator for pre-freezing for 24 hours, and then put it into a vacuum freeze dryer at -70°C for 24 hours to obtain the adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
[0045] Example 4
[0046] (1) While stirring, slowly add 145 mL of 0.8 mol / L sodium silicate solution to 100 mL of 25% hydrochloric acid aqueous solution. The pH value is measured to be 4.72.
[0047] (2) Gradually add 2.5% water-soluble chitosan (90% deacetylation degree), stir to dissolve, and react for 3 hours to obtain modified polysilicic acid.
[0048] (3) Add 1.7% PEG-400 to the modified polysilicic acid and then (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1:0.8, gradually add aluminum salt, magnesium salt and lanthanum salt, stir well and evenly to obtain a modified polysilicate aluminum magnesium lanthanum mixed solution. Among them, the aluminum salt is polyaluminum chloride, the magnesium salt is magnesium chloride hexahydrate, and the lanthanum salt is lanthanum chloride.
[0049] (4) Add the modified polysilicate aluminum magnesium lanthanum mixture dropwise into 500 mL of 25% mass concentration sodium carbonate solution and soak for 24 hours.
[0050] (5) Rinse with pure water, control the surface moisture, first put it into the freezer layer of the refrigerator for pre-freezing for 24 hours, and then put it into a vacuum freeze dryer at -70°C for freeze-drying for 24 hours to obtain the adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
[0051] Example 5
[0052] (1) While stirring, slowly add 170 mL of 0.5 mol / L sodium silicate solution to 100 mL of 20% hydrochloric acid aqueous solution. The pH value is measured to be 3.42.
[0053] (2) Gradually add 3% water-soluble chitosan (90% deacetylation degree), stir to dissolve, and react for 2 hours to obtain modified polysilicic acid.
[0054] (3) Add 2% PEG-600 to the modified polysilicic acid and then (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1:0.8, gradually add aluminum salt, magnesium salt and lanthanum salt, stir well and evenly to obtain a modified polysilicate aluminum magnesium lanthanum mixed solution. Among them, the aluminum salt is polyaluminum chloride, the magnesium salt is magnesium chloride hexahydrate, and the lanthanum salt is lanthanum chloride.
[0055] (4) Add the modified polysilicate aluminum magnesium lanthanum mixture dropwise into 500 mL of 25% mass concentration sodium carbonate solution and soak for 24 hours.
[0056] (5) Rinse with pure water, control the surface moisture, first put it into the freezer layer of the refrigerator for pre-freezing for 24 hours, and then put it into a vacuum freeze dryer at -70°C for freeze-drying for 24 hours to obtain the adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
[0057] In order to highlight the beneficial effects of the present invention, the following comparative example experiments are given.
[0058] Comparative Example 1
[0059] (1) While stirring, slowly add 170 mL of 0.5 mol / L sodium silicate solution to 100 mL of 20% hydrochloric acid aqueous solution. The pH value is measured to be 3.45.
[0060] (2) 2% chitosan (55% deacetylation degree) was gradually added. It was difficult to dissolve under stirring at room temperature and had a high viscosity, so the next step of the reaction could not be carried out.
[0061] Comparative Example 2
[0062] (1) While stirring, slowly add 170 mL of 0.5 mol / L sodium silicate solution to 100 mL of 20% hydrochloric acid aqueous solution. The pH value is measured to be 3.4.
[0063] (2) According to n(Si) :n (Al) :n (Mg) :n (La) =1:1.5:1:0.8, gradually add aluminum salt, magnesium salt and lanthanum salt, stir well and evenly to obtain polysilicate aluminum magnesium lanthanum solution. Among them, the aluminum salt is polyaluminum chloride, the magnesium salt is magnesium chloride hexahydrate, and the lanthanum salt is lanthanum chloride.
[0064] (3) Add the modified polysilicate aluminum magnesium lanthanum solution drop by drop into 500 mL of 20% mass concentration sodium carbonate solution and soak for 24 hours.
[0065] (4) Rinse with pure water, control the surface moisture, place in the freezer of the refrigerator for pre-freezing for 24 hours, and then place in a vacuum freeze dryer at -70°C for lyophilization for 24 hours. The obtained polysilicon aluminum magnesium lanthanum is in powder form.
[0066] Comparative Example 3
[0067] (1) While stirring, slowly add 175 mL of 0.5 mol / L sodium silicate solution to 100 mL of 20% hydrochloric acid aqueous solution. The pH value is measured to be 3.46.
[0068] (2) Gradually add 2% water-soluble chitosan (deacetylation degree 90%), stir to dissolve, and react for 2 hours to obtain modified polysilicic acid.
[0069] (3) According to n (Si) :n (Al) :n (Mg) :n (La) =1:1.5:1:0.8, aluminum salt, magnesium salt and lanthanum salt are gradually added, and the obtained modified polysilicate aluminum magnesium lanthanum mixed solution is in the form of gel mass. Among them, the aluminum salt is polyaluminum chloride, the magnesium salt is magnesium chloride hexahydrate, and the lanthanum salt is lanthanum chloride.
[0070] Comparative Example 4
[0071] (1) While stirring, slowly add 165 mL of 0.5 mol / L sodium silicate solution to 100 mL of 20% hydrochloric acid aqueous solution. The pH value is measured to be 3.4.
[0072] (2) Gradually add 2% water-soluble chitosan (deacetylation degree 90%), stir to dissolve, and react for 2 hours to obtain modified polysilicic acid.
[0073] (3) Add 1.2% PEG-20000 to the modified polysilicic acid and then (Si) :n (Al) :n (Mg) :n (La)=1:1.5:1:0.8, gradually add aluminum salt, magnesium salt and lanthanum salt, stir well and evenly, and obtain a viscous modified polysilicate aluminum magnesium lanthanum mixed solution. Among them, the aluminum salt is polyaluminum chloride, the magnesium salt is magnesium chloride hexahydrate, and the lanthanum salt is lanthanum chloride.
[0074] (4) Add the modified polysilicate aluminum magnesium lanthanum mixed solution drop by drop into 500 mL of 20% mass concentration sodium carbonate solution. Due to the high viscosity, the dripped particles are large. Soak for 24 hours.
[0075] (5) Rinse with pure water, control the surface moisture, first put it into the freezer layer of the refrigerator for pre-freezing for 24 hours, and then put it into a vacuum freeze dryer at -70°C for 24 hours to obtain adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
[0076] The adsorption-type defluoridating agents prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to performance tests on defluoridation rate, adsorption capacity and regeneration efficiency for fluoride-containing water samples of different concentrations. The test method was based on GB / T 7484-1987 "Determination of fluoride in water - Ion-selective electrode method". The final calculation results are listed in Tables 1 and 2; Table 1 is a test for an aqueous solution with a fluoride content of 5 mg / L, and Table 2 is a test for an aqueous solution with a fluoride content of 20 mg / L.
[0077] Table 1 Fluoride removal rate of aqueous solution with fluoride content of 5 mg / L
[0078] Table 2 Fluoride removal rate of aqueous solution with fluoride content of 20 mg / L
[0079] It can be seen from the data in Table 1-2 that the adsorption-type defluoridation agent prepared in Examples 1-5 has significantly improved fluorine removal rate, adsorption capacity and regeneration efficiency compared with Comparative Examples 1-4, especially for water samples with high fluorine content, the adsorption-type defluoridation agent of the present invention has a more excellent effect.
[0080] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an adsorption-type defluorinating agent, characterized in that: The following steps are involved: (1) Slowly add sodium silicate solution to the hydrochloric acid aqueous solution under stirring to control the pH to 3-5; (2) gradually adding polyhydroxy polymer organic matter, stirring to dissolve, and reacting for 1 to 3 hours to obtain modified polysilicic acid; (3) adding a water-soluble dispersant to the modified polysilicate, and then gradually adding aluminum salt, magnesium salt, and lanthanum salt, and stirring well to obtain a modified polysilicate aluminum magnesium lanthanum mixed solution; (4) Add the modified polysilicate aluminum magnesium lanthanum mixed solution drop by drop into the sodium carbonate solution and soak for 12 to 24 hours; (5) Rinse with pure water, control the surface moisture, first put it into the freezer of the refrigerator for pre-freezing, and then put it into a vacuum freeze dryer for freeze-drying to obtain the adsorption-type defluorination agent modified polysilicon aluminum magnesium lanthanum particles.
2. The method for preparing an adsorption-type defluorinating agent according to claim 1, characterized in that: In the step (1), the mass fraction of the hydrochloric acid aqueous solution is 10% to 25%, and the concentration of the sodium silicate solution is 0.3 to 1 mol / L.
3. The method for preparing the adsorption-type defluorinating agent according to claim 1, characterized in that: In the step (2), the polyhydroxy polymer organic matter is one or more of water-soluble chitosan, sodium carboxymethyl cellulose, sodium alginate, pectin, and polyvinyl alcohol.
4. The method for preparing the adsorption-type defluorinating agent according to claim 1, characterized in that: In the step (2), the amount of polyhydroxy polymer organic matter added is 0.5% to 3%.
5. The method for preparing the adsorption-type defluorinating agent according to claim 1, characterized in that: In the step (3), the dispersant is one or more of polyethylene glycol, lignin sulfonate, polyethylene imine, and dodecyl dimethyl betaine; wherein the average molecular weight of the polyethylene glycol is 400-4000; and the amount of the dispersant added is 0.2%-2%; The aluminum salt is one or more of crystalline aluminum chloride, anhydrous aluminum chloride, polyaluminum chloride, polysulfide aluminum chloride, polyaluminum ferric chloride, basic aluminum chloride, aluminum sulfate, polyaluminum sulfate, alum, and aluminum nitrate; The magnesium salt is one or more of magnesium chloride hexahydrate, magnesium carbonate, magnesium sulfate, magnesium nitrate, and magnesium citrate; The lanthanum salt is one or more of lanthanum chloride, lanthanum nitrate, lanthanum carbonate, lanthanum sulfate, and lanthanum oxalate.
6. The method for preparing the adsorption-type defluorinating agent according to claim 1, characterized in that: In step (3), n (Si) :n (Al) :n (Mg) :n (La) =1:1.5~2.5:0.5~1.5:0.3~0.
8.
7. The method for preparing the adsorption-type defluorinating agent according to claim 1, characterized in that: In the step (4), the mass concentration of sodium carbonate is 10% to 25%.
8. The method for preparing the adsorption-type defluorinating agent according to claim 1, characterized in that: In the step (5), the freeze-drying temperature is -50 to -70°C, and the freeze-drying time is 12 to 24 hours.
9. An adsorption-type defluorinating agent obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the adsorption-type defluoridating agent according to claim 9 in the treatment of fluorine-containing wastewater.
Citation Information
Cited By
Fluorine ion visual adsorption material as well as preparation method and application thereof
CN120005218A